Processing parameters involved in the development of texture and tyrosine precipitates in dry-cured ham: Modelisation of texture development. (February 2021) - Coll-Brasas, E.; Gou, P.; Arnau, J.; Olmos, A.; Fulladosa, E.
Abstract: The aim of this study was to quantify the effects of different processing parameters on texture development and the incidence of white film and tyrosine crystals in dry-cured ham. Hams were dry-salted for 0.65, 0.8 or 1.0 days/kg. After drying for 45 days at 5 °C, they were dried at 10, 15 or 20 °C until reaching 33% weight loss and, thereafter, dried at 25 °C until reaching 36 or 40% weight loss. The salting time, drying temperature and target weight loss significantly affected the texture and incidence of white film and tyrosine crystals. A beneficial effect of drying at 20 °C on texture was found, which was especially important for low target weight loss (33%). Besides, hams dried at 20 °C and those with 40% weight loss showed higher incidence of tyrosine crystals. Contour plots and predictive models for texture can be used to define optimal processing parameters